(untitled) (Research, Society and Development, 2021)
The aim of this review was to identify what is being considered when using blockchain for sharing of health records. The BVS and PubMed databases were screened by articles published between July 2018 and July 2021. A total of eight studies, in which patients own the data and have access to it, were selected. It was observed that data confidentiality was the main concern (87.5%), followed by scalability (25%), latency (25%), and availability (12.5%). It was concluded that despite all the advantages associated with the use of Blockchain, data reliability still stands out as one of the concerns when using it for sharing health records.